La Caricature, 1830-1835 : lithographies complètes : an illustrated catalogue raisonné of the lithographs - Labridy-Stofle, Corine; Labridy-Stofle, Corine; Labridy-Stofle, Corine; Philipon, Charles (Alan Wofsy Fine Arts, 2017)
La Caricature' was the 19th Century equivalent and the precursor of Charlie Hebdo. The editor Charles Philipon employed the major satirical artists of the mid-19th Century notably Daumier, Grandville, E. Forest, Charlet, Bellangé , Traviès, Raffet and Gavarni. It appeared for five years, between 1830-1835. The main subjects of the caricatures were Louis-Philippe and his entourage of July Monarchy politicians. Louis-Philippe, son of the Duke of Orléans, came to power after the 1830 Revolution as the Citizen King. However, he was not amused by the caricatures and once put Daumier in prison for 6 months, before suppressing the whole publication in 1835. He became more and more authoritarian and was finally forced to abdicate during the 1848 Revolution. The plates are numbered 1-524, but approximately 62 are double sheets so there are actually 462 separate prints. Georges Vicaire catalogued the 251 issues and 524 plates in 1895. However they have never been reproduced in a catalogue, nor has there been an English language discussion or catalogue of the corpus of prints. All of the works are described in French and English and are arranged in the order they appeared in the original publication. There is an index by artist and the catalogue by Georges Vicaire from 1895 is also included. Many of the artists contributed anonymously and were not identified by Vicaire but are now identified. Where there were not descriptions of the plates in the original publication (about 60 of the 462) , this new edition now provides descriptions in French